The Highway Capacity Manual: A Conceptual and Research History Volume 1: Uninterrupted Flow - Roess, Roger . P. (Springer Tracts on Transportation and Traffic, 2014)
Since 1950, the Highway Capacity Manual has been a standard used in the planning, design, analysis, and operation of virtually any highway traffic facility in the United States. It has also been widely used abroad, and has spurred the development of similar manuals in other countries. The twin concepts of capacity and level of service have been developed in the manual, and methodologies have been presented that allow highway traffic facilities to be designed on a common basis, and allow for the analysis of operational quality under various traffic demand scenarios. The manual also addresses related pedestrian, bicycle, and transit issues. Â  This book details the fundamental development of the concepts of capacity and level of service, and of the specific methodologies developed to describe them over a wide range of facility types. The book is comprised of two volumes. Volume 1 (this book) focuses on the development of basic principles, and their application to uninterrupted flow facilities: freeways, multilane highways, and two-lane highways. Weaving, merging, and diverging segments on freeways and multilane highways are also discussed in detail. Volume 2 focuses on interrupted flow facilities: signalized and unsignalized intersections, urban streets and arterials. It is intended to help users of the manual understand how concepts, approaches, and specific methodologies were developed, and to understand the underlying principles that each embodies. It is also intended to act as a basic reference for current and future researchers who will continue to develop new and improved capacity analysis methodologies for many years to come.